Hak Merek Sebagai Jaminan Fidusia Dalam Praktik Pemberian Kredit Oleh Perbankan Di Indonesia - Wely Saputra; Muhammad Yasir (JOURNAL of LEGAL RESEARCH, 2020)
The goal of this study is to develop the legal status of brand rights as collateral for bank credit guarantees and to analyze the risks of applying brand rights as collateral for bank credit guarantees in Indonesia. Brand rights are part of intellectual property rights which, of course, are of commercial significance to be used as collateral for bank loans. This study is a normative legal research using a regulatory methodology or a legislative approach to interpreting the idea of brand rights being used as security for bank loan guarantees, as laid down in statutory regulations, which are meant to try to get closer to the problems examined on the basis of laws, norms and rules. In compliance with the purpose of the analysis. The findings of the research suggest that Brand Rights can potentially be used as collateral for bank credit guarantees in compliance with the relevant legal requirements, but there are no specific laws and regulations that explicitly govern brands used as collateral for bank credit and, as a result, many banks in Indonesia have not been able to consider brands as collateral for bank credit guarantees.